2014
DOI: 10.1016/j.jbiomech.2013.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Tensile properties of the medial patellofemoral ligament: The effect of specimen orientation

Abstract: For recurrent patellar dislocation, reconstruction of the medial patellofemoral ligament (MPFL) with replacement autografts has often been performed but with only little data on the tensile properties of the MPFL to guide graft selection. With its complex anatomy and geometry, these properties are difficult to obtain. In this study, we showed how the orientation of the femur-MPFL-patella complex (FMPC) during uniaxial tensile testing can have a significant effect on its structural properties. Twenty two FMPCs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 22 publications
0
27
0
2
Order By: Relevance
“…As found by Kim et al in a porcine study [16], the natural orientation mimics the in situ loading condition of the MPFL and should be used to obtain representative data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As found by Kim et al in a porcine study [16], the natural orientation mimics the in situ loading condition of the MPFL and should be used to obtain representative data.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [16] demonstrated that 90 % of failures at the femoral attachment of the native MPFL, where there is the narrowest portion of the ligament. In our study, we found 89 % of failure at the graft midsubstance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young adults (17–45 years) are at higher risk for ACL injury, especially those who are active in pivoting sports, such as soccer and skiing [46]. In most cases, the ACL injury occurs during sports participation and usually follows an abrupt deceleration, i.e., jumping or sideways cutting [7, 8].…”
Section: Introductionmentioning
confidence: 99%